2018
DOI: 10.1590/0101-60830000000163
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between panic disorder and plasma neuropeptide-S level

Abstract: Background: Panic disorder has long been associated with the changes in various neurotransmitters, such as Neuropeptide-S (NPS). Objective: In this study we aimed to determine whether there is a relationship between blood NPS levels and panic disorder. Methods: Twenty nine patients with panic disorder and thirty two healthy control subjects who were age and gender matched were enrolled to the study. Blood samples were taken from participants and plasma NPS levels were quantified by using an ELISA kit. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The study was limited only to male participants to reduce the risk of potential gender differences in NPS levels, which could not be corrected reliably between relatively small groups. Previous NPS studies with a limited number of participants clearly indicated difficulties in interpreting the results in relation to gender [ 19 , 20 , 25 ]. Moreover, PANSS results can also be influenced by gender differences [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was limited only to male participants to reduce the risk of potential gender differences in NPS levels, which could not be corrected reliably between relatively small groups. Previous NPS studies with a limited number of participants clearly indicated difficulties in interpreting the results in relation to gender [ 19 , 20 , 25 ]. Moreover, PANSS results can also be influenced by gender differences [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the anxiolytic effect is not related to excessive sedation, but rather to an increase in activity (“novel activating anxiolytic”), which is a pharmacologically unique feature [ 17 ]. The median plasma NPS level was found to be significantly higher in generalized anxiety disorder (GAD) patients [ 19 ]. While NPS may have a beneficial effect on anxiety, no direct effect on depression has yet been demonstrated in animal models [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the anxiolytic effect is not related to excessive sedation, but rather to an increase in activity ("novel activating anxiolytic"), which is a pharmacologically unique feature [21]. The median plasma NPS level was found to be significantly higher in generalized anxiety disorder (GAD) patients [23]. While NPS may have a beneficial effect on anxiety, no direct effect on depression has been demonstrated thus far in animal models [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, no studies on the relationship between plasma NPS in patients with schizophrenia and any type of treatment have been published so far. Although investigations of NPS's permeability from the blood-brain barrier have not been conducted on human subjects, the rationality of measuring plasma NPS level in patients with mental disorders has been demonstrated [23].…”
Section: Introductionmentioning
confidence: 99%